Major Asset Classes: A Brief Glossary - Jarrett Tsai; Jorge Ruiz-Menjivar; Martie Gillen (EDIS, 2019)
The best time to have started investing is yesterday. Whether you are saving for retirement, to send your child to college or for a down payment on a house, it can only be in your benefit to choose and implement the proper investment plan. But before one can actually make an informed decision on which financial vehicles to select for an investment portfolio or plan, it is pivotal to know about the options available in the market, and to clearly understand the main idea and principles behind each of these investment vehicles. There are entire books written on these topics, but for the purpose of this article, we aim to provide a brief, yet comprehensive glossary of the main financial investment vehicles.